Polonia w Stambule: imigranci w globalnym świecie, tożsamość i obywatelstwo w drodze transnarodowych przestrzeni społecznych. - Kłopocki, Michał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In the article, the author analyses the community of Polish immigrants in Istanbul: as descendents of the refuges who settled near Istanbul in Adampol in 19th century, as well as modern immigrants living in the city. Having briefly described the former, the author focuses on the latter group, finally comparing the two communities, which allows to rethink some immigration processes in modern Europe. Next, the integration processes and institutions which enable these processes are described. Finally, the author shows how artistic spaces, playing crucial role in sustaining Polishness, are created.